2014
DOI: 10.1021/ja412533d
|View full text |Cite
|
Sign up to set email alerts
|

“Conformation Locked” Strong Electron-Deficient Poly(p-Phenylene Vinylene) Derivatives for Ambient-Stable n-Type Field-Effect Transistors: Synthesis, Properties, and Effects of Fluorine Substitution Position

Abstract: The charge carrier mobility of p-type and ambipolar polymer field-effect transistors (FETs) has been improved substantially. Nonetheless, high-mobility n-type polymers are rare, and few can be operated under ambient conditions. This situation is mainly caused by the scarcity of strong electron-deficient building blocks. Herein, we present two novel electron-deficient building blocks, FBDOPV-1 and FBDOPV-2, with low LUMO levels down to -4.38 eV. On the basis of both building blocks, we develop two poly(p-phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
264
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 320 publications
(273 citation statements)
references
References 51 publications
7
264
0
2
Order By: Relevance
“…The first diffraction peaks (100) appear at 2 θ = 2.53 and 4.34° for TPE-1 and TPE-2, with interlayer distances of 20.07 Å and 35.31 Å, respectively. These results demonstrated that the thin film of TPE-2 takes a predominantly well-organized stacking structure along the vertical orientation, which is well-known to achieve a high carrier mobility 28 because of the intermolecular interactions parallel to the direction of the channel current flow in the PSC devices. 29 Thus, the increase of J sc of TPE-2 compared to that of TPE-1 should be ascribed to the higher electron transporting ability and lower contact resistance, mainly due to its compact and well-organized lamellar structure.…”
mentioning
confidence: 78%
“…The first diffraction peaks (100) appear at 2 θ = 2.53 and 4.34° for TPE-1 and TPE-2, with interlayer distances of 20.07 Å and 35.31 Å, respectively. These results demonstrated that the thin film of TPE-2 takes a predominantly well-organized stacking structure along the vertical orientation, which is well-known to achieve a high carrier mobility 28 because of the intermolecular interactions parallel to the direction of the channel current flow in the PSC devices. 29 Thus, the increase of J sc of TPE-2 compared to that of TPE-1 should be ascribed to the higher electron transporting ability and lower contact resistance, mainly due to its compact and well-organized lamellar structure.…”
mentioning
confidence: 78%
“…433 By introducing fluorine atoms on IBDF, Pei et al synthesized two new polymers P352 and P353 via microwave-assisted Stille coupling. 137 In comparison to the LUMO (−4.1 eV) of P351, IBDF fluorination effectively lowers the LUMOs of P352 and P353 to ∼−4.3 eV, which are among the lowest for polymer semiconductors. It was found that fluorination not only enables the low-lying LUMO but also greatly promotes polymer packing.…”
Section: Isoindigo Derivatives-based Polymer Semiconductors For Otftsmentioning
confidence: 99%
“…2013 年, 裴坚课题组首次报道了一类新型的含有 苯并二呋喃二酮的 PPV 衍生物, 简称 BDPPV [77] . 在空 气中, 其顶栅 OFET 器件展现出优异的 n-型电荷传输性 能, 其电子迁移率高达 1.1 cm [78] . 研究表明:…”
Section: 有机场效应晶体管主要由衬底(Substrate)、绝缘层 (Dielectric Layer)、有机半导体层(organunclassified